The effects of blood flow restriction training on post activation potentiation and upper limb muscle activation: a meta-analysis - Liu, Haiyang; Jiang, Lizhu; Wang, Jian (Frontiers in Physiology, 2024)
Objective: This meta-analysis aims to systematically evaluate the impact of blood flow restriction training (BFRT) on muscle activation and post-activation potentiation (PAP) in the upper limbs, to provide guidance for upper limb protocols aiming to enhance explosive strength and activation. Methods: PubMed, CNKI, Web of Science, and EBSCO databases were queried to identify randomized controlled trials (RCTs) investigating the effects of upper limb BFRT on muscle activation and PAP. Inclusion and exclusion criteria were applied using the Cochrane bias risk tool. Literature quality assessment and statistical analysis were conducted using Revman 5.4 and Stata 17.0 software. Sensitivity analysis and funnel plots were utilized to assess result stability and publication bias. Results: A total of 31 articles involving 484 participants were included in the analysis. Meta-analysis results showed that upper limb BFRT significantly increased muscle iEMG values [SMD=0.89, 95%CI (0.21,1.58), P =0.01]. BFRT had a significant effect on upper limb explosive force [SMD=0.73, 95%CI (0.41,1.04), P <0.00001]. Subgroup analysis based on literature heterogeneity (I 2 =92%, 80%) showed that exhaustive BFRT significantly decreased upper limb iEMG [SMD= -0.67, 95%CI (-1.25,-0.09), P =0.01], with exercise modes including maximum output power of bench press [SMD=1.87, 95%CI (0.22,3.53), P <0.0001], exercise intensity of 40%~70% 1RM [SMD=1.31, 95%CI (0.61,2.01), P <0.0001], and pressure intensity of ≥60% AOP [SMD=0.83, 95%CI (0.43,1.23), P <0.0001] reaching maximum effects and statistical significance. Conclusion: Upper limb BFRT can induce muscle activation and PAP. BFRT with 40%~70% 1RM and ≥60% AOP in the upper limbs is more likely to promote PAP.